The Analysis of Heroes’ Traits in Percy Jackson and the Olympians: The Lightning Thief - Ma'ruf, Annaz (English Literature Study Program, 2023)
This research analyzed the heroic portrayal of the main character, Percy Jackson, in Rick Riordan's novel